Reporting Under the International Convention for the Protection of All Persons From Enforced Disappearance - United Nations for Human Rights Office of the High Commissioner (United Nations, 2022)
This Training Guide seeks to assist States parties in meeting their obligations to respect, protect and fulfil the rights enshrined in the Convention for the Protection of all Persons against Enforced Disappearances. The Manual, which is the first part of the Training Guide, outlines the provisions of the Convention and provides useful guidance on the content and scope of the rules of procedure and the working methods of the Committee on Enforced Disappearances, as well as reporting obligations under the Convention. The publication draws on the wealth of experience acquired by the Committee over the years. It highlights practical examples on the submission of information and data under the Convention and the successful implementation of Committee’s recommendations. These examples would be of use to States parties and, in particular, to those involved in the delivery of training courses on reporting to the Committee and on the implementation of the Convention. By promoting a greater understanding of the provisions of the Convention, the Training Guide aims to provide guidance and support to reporting States as to the content of reports and the implementation of recommendations. The Manual will be complemented by training materials (Part II), tailored to each of the Convention’s rights, to be published on the OHCHR website.